(untitled) (Advancements in Homeopathic Research, 2023)
Fibromyalgia is a condition which has widespread musculoskeletal pain with fatigue, cognitive disturbance, psychiatric and multiple somatic symptoms. There is no evidence of tissue inflammation despite symptoms of soft tissue pain. This article deals with clinical presentation of fibromyalgia as well as its approach in clinical repertories which are commonly used like Boreicke repertory and Phatak repertory.